Conceptions on gender of undergraduate students in Pedagogy from the Free Association of Words - Ferreira da Silva, Matheus Estevao [UNESP]; Antonelli Marcelino Brabo, Tania Suely [UNESP]; Morais, Alessandra de [UNESP] (Univ Nove Julho, 2022)
The objective is to analyze the conceptions of undergraduate students in Pedagogy, from a public university in Sao Paulo, about gender. Data collected through an open questionnaire was used, using the Free Word Association Technique (TALP). The participants consisted of 165 undergraduates enrolled in the initial and final years of the course. A word association test was generated in which the words associated with gender had their evocation frequency calculated and were grouped according to their meaning parity. Six conceptions were created: gender in 1) polysemic conception; 2) biologizing; 3) critical-social; 4) identity; 5) religious-radical; and 6) associated with sexuality; being the most predominant, with more words evoked and more frequently, the identity and critical-social conceptions. The results revealed that the theme, being conceived in different ways, varies from less emancipatory perspectives to others more potential for the development of a pedagogical work that addresses gender at school.
Keywords: education; genre; teacher training; pedagogy; free association of words